2017
DOI: 10.1093/gji/ggx061
|View full text |Cite
|
Sign up to set email alerts
|

Deep ocean sound speed characteristics passively derived from the ambient acoustic noise field

Abstract: S U M M A R YThe propagation of acoustic waves in the ocean strongly depends on the temperature. Lowfrequency acoustic waves can penetrate the ocean down to depths where few in situ measurements are available. It is therefore attractive to obtain a measure of the deep ocean temperature from acoustic waves. The latter is especially true if the ambient acoustic noise field can be used instead of deterministic transient signals. In this study the acoustic velocity, and hence the temperature, is derived in an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This lag time error can be estimated from a particular non-isotropic distribution of recorded wave intensity (Froment et al 2010). Recent studies by Woolfe et al (2015) and Evers et al (2017) are probably affected by similar uncertainties, however, the relative errors are much smaller due to the much longer lengthscale, with intersensor distances greater than 100 km. The concept of thermometry, even for such small receiver distances, can be improved by retrieving stationary lag times of multiple sources (Snieder et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This lag time error can be estimated from a particular non-isotropic distribution of recorded wave intensity (Froment et al 2010). Recent studies by Woolfe et al (2015) and Evers et al (2017) are probably affected by similar uncertainties, however, the relative errors are much smaller due to the much longer lengthscale, with intersensor distances greater than 100 km. The concept of thermometry, even for such small receiver distances, can be improved by retrieving stationary lag times of multiple sources (Snieder et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned sources confine the dominant sources of the hydroacoustic network's ambient noise field. Recent studies have shown the potential of passive hydroacoustic thermometry in the SOFAR channel using traveltime variations of ridge earthquakes (Evers & Snellen 2015) and by crosscorrelating ambient signals recorded at two distinct IMS arrays, H10N and H10S, located near Ascension Island in the South Atlantic Ocean (Woolfe et al 2015;Evers et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the studies of Evers et al. (2017) and Takagi et al. (2015) indicate the presence of repetitive electronic noise of the H10 data loggers causing spurious coherent cross‐correlations.…”
Section: Instrumentationmentioning
confidence: 99%